TikTok and frozen shoulder: a cross-sectional study of social media content quality - Riccardo D’Ambrosi; Enrico Bellato; Gianluca Bullitta; Antonio Benedetto Cecere; Katia Corona; Angelo De Crescenzo; Valentina Fogliata; Gian Mario Micheloni; Maristella Francesca Saccomanno; Fabrizio Vitullo; Andrea Celli; SICSeG (Italian Society of Shoulder, Elbow Surgery) Research Committee (Journal of Orthopaedics and Traumatology)
Abstract Purpose This study aimed to assess the validity and informational value of the material provided on TikTok regarding frozen shoulders. The hypothesis was that the video content on this platform would not provide adequate and valid information. Methods The current study focused on frozen shoulder videos on the TikTok social media platform. The terms “frozen shoulder” and/or “adhesive capsulitis” were used as keywords for an extensive online search of video content on TikTok, and the first 100 videos were included. Out-of-topic, non-English, and duplicated videos were excluded from the analysis. The duration and numbers of likes, shares, and views were recorded for each video. Further, videos were categorized based on the source (physiotherapist/osteopath, medical doctor, or private user), type of information (physical therapy, etiopathogenesis, anatomy, clinical examination, patient experience, or symptoms), video content (rehabilitation, education, or patient experience/testimony), and the presence of music or a voice. The assessment of the video content’s quality and reliability was performed by two experienced shoulder surgeons using the DISCERN instrument, the Journal of the American Medical Association (JAMA) benchmark criteria, and the Global Quality Score (GQS). Results A total of 100 videos were included in the analysis, of which 86 (86.0%) were published by physiotherapists/osteopaths. Most of the information and video content focused on physical therapy and rehabilitation (83.0% and 84.0%, respectively). Eighty-four (84.0%) videos included voice comments, while the remaining featured music. The mean number of views was 2,142,215.32 ± 6,148,794.63, while the mean numbers of likes, comments, and shares were 58,438.67 ± 201,863.54, 550.81 ± 1712.22, and 3327.43 ± 7320.81, respectively. The mean video duration was 110.20 ± 116.43 s. The mean DISCERN score, JAMA score, and GQS were 16.17 ± 2.36, 0.61 ± 0.51, and 1.18 ± 0.41, respectively. Videos posted by medical doctors or private users received higher scores than those posted by physiotherapists/osteopaths (p < 0.05). Conclusions The educational value of videos published on TikTok was poor; videos posted by medical doctors exhibited better quality and educational value than those of physiotherapists or osteopaths. It is the responsibility of orthopedic surgeons to investigate the potential benefits, consequences, and implications of TikTok video content for the health of frozen shoulder patients and to propose necessary adjustments. Given the rapid growth of TikTok, further research is needed. Level of evidence Level IV—cross-sectional study.